Sulphur and carbon cycling in the subduction zone mélange. Issue 1 (December 2018) - Schwarzenbach, Esther; Caddick, Mark; Petroff, Matthew; Gill, Benjamin; Cooperdock, Emily; Barnes, Jaime
Abstract Subduction zones impose an important control on the geochemical cycling between the surficial and internal reservoirs of the Earth. Sulphur and carbon are transferred into Earth's mantle by subduction of pelagic sediments and altered oceanic lithosphere. Release of oxidizing sulphate- and carbonate-bearing fluids modifies the redox state of the mantle and the chemical budget of subduction zones. Yet, the mechanisms of sulphur and carbon cycling within subduction zones are still unclear, in part because data are typically derived from arc volcanoes where fluid compositions are modified during transport through the mantle wedge. We determined the bulk rock elemental, and sulphur and carbon isotope compositions of exhumed ultramafic and metabasic rocks from Syros, Greece. Comparison of isotopic data with major and trace element compositions indicates seawater alteration and chemical exchange with sediment-derived fluids within the subduction zone channel. We show that small bodies of detached slab material are subject to metasomatic processes during exhumation, in contrast to large sequences of obducted ophiolitic sections that retain their seafloor alteration signatures. In particular, fluids circulating along the plate interface can cause sulphur mobilization during several stages of exhumation within high-pressure rocks. This takes place more pervasively in serpentinites compared to mafic rocks.